Peran Gaya Kepemimpinan dan Komunikasi Organisasi terhadap Kinerja Pegawai dalam Reformasi Birokrasi Di Kabupaten Banggai Laut - Rahmawaty Rahman Pattiwael; Arlin Adam; Andi Alim (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
This study aims to explore the socio-cultural dynamics in the implementation of bureaucratic reform in regional health services, focusing on the role of leadership styles and organizational communication in influencing employee performance at the Department of Health, Population Control, and Family Planning in Banggai Laut Regency. A qualitative case study approach was used, employing in-depth interviews, limited participant observation, and document analysis. The results indicate that local values such as kinship, hierarchy, deliberation, and mutual cooperation continue to influence bureaucratic processes, both as strengths and as challenges. Participatory leadership styles and two-way communication patterns significantly enhance work motivation, collaboration, and accountability. Organizational culture shaped by local values supports internal cohesion, although challenges remain, including resistance to change and limited human resource capacity. Strategies implemented to improve organizational performance include exemplary leadership, continuous training, an open and innovative work climate, and the integration of local cultural values with modern governance principles. The study concludes that the success of bureaucratic reform in the health sector at the regional level depends heavily on the organization's ability to synergize local wisdom with professional bureaucratic standards.